THE EFFECTIVENESS OF USING CHUNKING STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION AT THE SECOND YEAR OF SMP NEGERI 2 BAROMBONG - Rini Anggraini (Universitas Islam Negeri Alauddin Makassar, 2015)
The objective of this research was to know whether chunking strategy effective to improve students’ reading comprehension of the second year of SMP Negeri 2 Barombong and found the students’ attitude in learning using chunking strategy. The research design applied non-equivalent control group design which is one of the forms of quasi experimental design consisting of two groups (Experimental group and controlled group) each group covering 6 meetings. This research focused on improving the students’ reading comprehension in comprehending narrative text. The instruments used were reading text, observation sheet, and questionnaire.Further, the data analysis techniqueused in this research was statisticalanalysis.The findings of this research showed that chunking strategy effective to improve the students reading comprehension in which the mean score of students’ post-test of experimental group was 56. It was higher than the controlled group that was only got 23.This research was successful to solve the students’ problem in comprehending thetextby using chunking strategy.